The Osmotic Response and Hydromineral Status of Transported Anguilla bicolor bicolor Glass Eels with Various Ratios of Biomass and Water Volume - Ferdinand Hukama Taqwa; Eddy Supriyono; Tatag Budiardi; Mia Setiawati; Bambang Priyo Utomo; Ridwan Affandi (Fisheries and Marine Science Faculty - Jenderal Soedirman University)
This research was conducted to determine the closed transportation system with biomass and water volume ratio that can support the osmoregulation ability of glass eel significantly. Glass eel was obtained from catching activities in the Cimandiri River, Pelabuhan Ratu (mean length 52.40+0.84 mm and weight 0.10+0.01 g) and acclimatized for 24 hours at salinity 6 mg L-1 and temperature 20°C gradually.The research design was a completely randomized design. The applied treatment was glass eel closed transportation system with various ratio of glass eel biomass (kg): water volume (L), i.e. 1:11; 1:12; 1:13; and 1:14 during 24 hours of land transportation and continued with a 3-day recovery period.The water was used refer to the above acclimatization method, with ratio the water part of pure oxygen in a plastic bag was 1:3. The measured parameters include survival rate, osmotic gradient, body hydromineral, and water quality in transport packaging and recovery medium. Survival rates were generated in the high range until recovery period (P<0.05), but the transportation method caused differences significantly (P<0.05) in osmotic response and hydromineral status (sodium, chloride, potassium, and water content), so that it will affect production performance in the next stage of culture. Ratio of glass eel biomass: water volume of 1:13 has been able to support the ability of osmoregulation glass eel to maintain homeostatic condition during the transportation until 3 days of recovery period. There was no drastic decline in physical and chemical value of water in the transport bag so it could reduce the mortality rate for 24 hours.